EARLY CONVERSION TO EVEROLIMUS IN RECIPIENTS OF KIDNEYS FROM EXPANDED CRITERIA DONORS - O. N. Reznik; A. N. Ananyev; I. V. Ulyankina (Вестник трансплантологии и искусственных органов)
This is preliminary report about first clinical experience with early conversion to Everolimus based scheme of immunosupression for kidney transplant recipients receiving grafts from expanded criteria donors (ECDs). The indications were given in aspects of recommended pretransplant estimation of zero-biopsy results. Two groups of recipients received grafts form the same suboptimal donors, n = 20, and were divided according to different scheme of immunosupression. The recipients of the first one, comparative group, n = 17, received standard CNI- based three components scheme, the recipients of the other one, investigation group, n = 20, received Everoli- mus based scheme of immunosupression, with cancelled MMF and reduction of CNI in two times. The statistic differences of the serum creatinine level were 215,3 ± 53,38 in comparative group and 149 ± 53,9 mkmol/L in investigation group (р = 0,022). Despite the benefits of early conversion to Everolimus in recipients of grafts from ECDs which were shown by authors this protocol demands further investigation.